Underrättelseskyldigheten i nordiska standardavtal för entreprenad - Bark,Felix (2019)
In this paper I have investigated the duty of notification in the Nordic standard contracts for contracting. The four agreements I have dealt with in my essay are AB 04, AB 92, AB 18 and NS 8405. The purpose of the thesis is to clarify the obligation to notify in the said standard agreements since they are very extensive and different in their design. My second goal was to clarify the differences between the various agreements and to carry out an analysis of how a potential future AB agreement might deal with the notification obligation. A shorter review of the duty of loyalty and its use was carried out to show where the notification obligation originated. The agreement in addition to AB 04 is the neighbouring countries Denmark and Norway's agreement. Like Sweden, they have a similar standard agreement with a similar design and an additional notification obligation. The most comprehensive review of the duty to notify has been made by AB 04. In that part I go through what penalties it can be if a party forgets to notify under given conditions. In addition to the more thorough review, I have outlined the Danish agreement in which AB 18 replaces the old agreement AB 92 since the beginning of the year. The choice of addressing both agreements is because I have, with a legal-analytical method, compared the development of the obligation of intelligence and analysed it together with a court case from the Supreme Court where they obtained guidance from Nordic contracts. The result of the paper was that I discovered ambiguities in how obligations to notify are treated between different authors and how they are handled between the different countries based on the idea that there should instead be a duty of cooperation and a duty of loyalty between the parties which constitute what AB 04 would qualify as an intelligence obligation. Finally, I concluded that the obligation may not be as prominent in a subsequent AB agreement, on the grounds that it is far too great a difference between the agreements and a lack of legal cases on the subject to find guidance.
Keywords: Underrättelsesskyldighet; Underrättelseplikt; Entreprenadrätt; AB 04; NS 8405; AB 92; AB 18